Strategi Promosi Umroh Plus Bebrbasis Kemitraan Holistik sebagai Upaya Eksistensi Daya Saing KBIH - Yuharso Hadi; Lukmansyah Lukmansyah; Ali Machrus (Prodi Ekomoni Syariah STAI Al Akbar Surabaya, 2025)
This research was conducted to address the challenges posed by the rapid development of information technology, which demands tour and travel companies to promote their products in innovative, creative, and effective ways. The impact of this technological advancement is particularly notable in the field of Hajj plus and Umroh, where the